2018 Vegetable Production Handbook Chapter 12: Onion, Leek, and Chive Production in Florida - Peter J. Dittmar; Eugene J. McAvoy; Monica Ozores-Hampton; Richard N. Raid; Pamela Roberts; Hugh A. Smith; Xavier Martini; Johan Desaeger; Joseph W. Noling; Shouan Zhang; Lincoln Zotarelli (EDIS, 2018)
This 19-page fact sheet is chapter 12 of the 2018 Vegetable Production Handbook. Written by Peter J. Dittmar, Eugene J. McAvoy, Monica Ozores-Hampton, Richard N. Raid, Pamela Roberts, Hugh A. Smith, Xavier Martini, Johan Desaeger, Joseph W. Noling, Shouan Zhang, and Lincoln Zotarelli, and published by the Horticultural Sciences Department, 2018.